Book Review: Globalization and Transnational Migrations: Africa and Africans in the Contemporary Global System - Monsuru O. Muritala (Journal of Global Initiatives, 2010)
Reviews the book Globalization and Transnational Migrations: Africa and Africans in the Contemporary Global System, edited by Akanmu.G Adebayo and Olutayo C. Adesina. Published by Cambridge Scholars Publishing, 2009.